Липкая инфляция, или языковая игра на материале словацких и российских экономических текстов - Vieriková, Lucia (Studia Rossica Posnaniensia, 2024)
In modern linguistics, the understanding of language game refers to the field of speech communication, and the language games themselves are seen as a decoration of speech. Language gaming is multifarious. In this article we will focus on some forms of this phenomenon, manifested in the variation of words, their forms and meanings in Russian and Slovak economic media texts. In modern economic media texts, textual “expressivization” is observed, which is realized primarily with the help of the language games. Its evaluative function comes to the forefront – evaluativity is an integral category of media language. In our article we will focus on examples of language games in Slovak and Russian economic texts, which, in our opinion, contain this evaluation. Language gaming is a misuse of words or letters, a breach of logical correspondence, but, very importantly, it is an incorrectness that is realized by the author and deliberately allowed. Only a deliberate incorrectness will cause not annoyance and bewilderment, but a desire to support the game and try to uncover the author’s underlying intention.